Analisis Kasus Stunting dan Faktor-faktor yang Berhubungan di Kampung Arowi Distrik Manokwari Timur - Suryana Widiastuti; Meike Meilan Lisangan; Ludia T. Wambrauw (Cassowary, 2021)
West Papua Province currently ranks 27 out of 34 Provisni in Indonesia with the prevalence of stunting cases. There are 3,141 children in West Papua with nutritional status with stunting in very short conditions, and 329 of them are in Manokwari Regency. East Manokwari District is one of the districts that has high stunting cases in Manokwari Regency. The purpose of this study was to determine the number of stunting cases in Arowi Village, East Manokwari District. The research method used in this research is quantitative descriptive method, which is a form of research based on data collected during research systematically regarding the facts, levels of participation and factors that influence in the East Manokwari district in Arowi village which will then be interpreted and tested based on theories and literatures. Based on the research on stunting cases in Arowi Village, it can be concluded that the number of stunting cases in Arowi Village, East Manokwari District reached 18% of the total number of respondents. The highest cases of stunting were found in the respondent population who had low knowledge of nutrition and in children who often experienced infectious diseases.